2022
DOI: 10.1136/bmjhci-2021-100423
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for developing a platform that evaluates algorithmic equity and accuracy

Abstract: We are at a pivotal moment in the development of healthcare artificial intelligence (AI), a point at which enthusiasm for machine learning has not caught up with the scientific evidence to support the equity and accuracy of diagnostic and therapeutic algorithms. This proposal examines algorithmic biases, including those related to race, gender and socioeconomic status, and accuracy, including the paucity of prospective studies and lack of multisite validation. We then suggest solutions to these problems. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…To ensure that all patients are ensured equal access to high-quality medical care, including surgical services, it is first necessary to analyze the data sets used to determine whether patients of color, women and those in lower socioeconomic groups are accurately represented in the data sets and algorithms used to determine the need for said services. As we have pointed out in a previous publication 26 , this has not always been the case. Obermeyer et al’s 27 analysis of a commercial database has demonstrated that, while Blacks were considerably sicker than White patients, based on signs and symptoms, the dataset did not recognize the greater disease burden in Blacks because it assigned risk scores based on total healthcare costs accrued.…”
Section: Can Surgical Bias Yield To Ai-based Algorithms?mentioning
confidence: 83%
See 1 more Smart Citation
“…To ensure that all patients are ensured equal access to high-quality medical care, including surgical services, it is first necessary to analyze the data sets used to determine whether patients of color, women and those in lower socioeconomic groups are accurately represented in the data sets and algorithms used to determine the need for said services. As we have pointed out in a previous publication 26 , this has not always been the case. Obermeyer et al’s 27 analysis of a commercial database has demonstrated that, while Blacks were considerably sicker than White patients, based on signs and symptoms, the dataset did not recognize the greater disease burden in Blacks because it assigned risk scores based on total healthcare costs accrued.…”
Section: Can Surgical Bias Yield To Ai-based Algorithms?mentioning
confidence: 83%
“…Commercially available AI bias detection tools that have been used to help identify discrimination include concept activation vectors (TCAV), which are used by Google to measure bias by race, gender, and location 31 , and Audit-AI, which uses a Python library from Pymetrics that can detect discrimination by locating specific patterns in the training data 26 , 32 .…”
Section: Can Surgical Bias Yield To Ai-based Algorithms?mentioning
confidence: 99%
“…128 This predicament can further amplify the enduring issue of model bias and inequality in medical research-an issue from which the field of allergy is not exempt, 129 as evident in models demonstrating lesser accuracy in underprivileged populations. 130 To alleviate this risk, three strategies are recommended. First, ideally, comprehensive data about a patient's environment, inclusive of historical allergen exposure, should be procured and included in the model training procedure.…”
Section: F I G U R Ementioning
confidence: 99%
“…Notable differences in sensitization patterns across geographical regions enhance this challenge 128 . This predicament can further amplify the enduring issue of model bias and inequality in medical research—an issue from which the field of allergy is not exempt, 129 as evident in models demonstrating lesser accuracy in underprivileged populations 130 . To alleviate this risk, three strategies are recommended.…”
Section: Current State Of Ai In the Allergy Research Fieldmentioning
confidence: 99%
“…To prevent the problems of infinite loop (feedback algorithm disorder failure)/zero divided amount/delay, the storage module and timing assignment module are properly designed in the model loop algorithm. Therefore, the mathematical model is the basis of this condenser model, and its accuracy and real-time directly affect the accuracy and speed of the model, so the establishment of the mathematical model is very important [5][6]. According to the structural characteristics of power plant condenser, this paper divides its mathematical model into shell side and tube side.…”
Section: Mathematical Model Of Condensermentioning
confidence: 99%